The Cognitive Trap of Rousseau's "Organic Metaphor" and the Construction of U.S. Policy in Europe and Eurasia - K. E. Koktysh; V. M. Sergeev; A. A. Igityan (Vestnik MGIMO-Universiteta)
The ideological dimension of international relations and foreign policy represents a distinct area of interaction, often situated at the intersection of political theory and philosophy. This study explores how metaphors, particularly Rousseau’s Organic Metaphor and its adaptation by Woodrow Wilson in his conceptualization of nationalism, function as powerful cognitive tools within the political sphere. These metaphors can act as "cognitive keys" that shape the perception of socio-political realities, influencing both the understanding and actions of political actors. However, while they provide a framework for understanding the internal logic of events, they also limit cognitive freedom by acting as implicit filters. This article traces the instrumental use of these metaphors in U.S. foreign policy, particularly how Wilson’s conceptualization of nationalism, derived from Rousseau’s metaphor, was utilized to reshape the ideational landscape of European politics in the 20th century and is now being applied in Eurasia. The concept of nationalism allowed for the fragmentation of competing political entities, aligning with the U.S. strategy of divide et impera to oppose integration movements. The article further examines how these strategies, which once targeted European empires, are now being employed against emerging integration unions in Eurasia, thereby highlighting the continuity of ideological tools in American foreign policy across different historical contexts.